2021
DOI: 10.1021/acsmacrolett.1c00354
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Formulation of Concentrated Semiconductive Fluid Using Polyelectrolyte Coacervation

Abstract: Conjugated polyelectrolytes (CPEs), which combine πconjugated backbones with ionic side chains, are intrinsically soluble in polar solvents and have demonstrated tunability with respect to solution processability and optoelectronic performance. However, this class of polymers often suffers from limited solubility in water. Here, we demonstrate how polyelectrolyte coacervation can be utilized for aqueous processing of conjugated polymers at extremely high polymer loading. Sampling various mixing conditions, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 53 publications
(67 reference statements)
2
41
0
Order By: Relevance
“…By probing the CPE photophysics, we can directly elucidate how the delocalized electronic wavefunction of the CPE evolves across the transition from the two‐phase to the one‐phase region of the phase diagram. To the best of our knowledge, our work is the first to demonstrate the formation of an aqueous complex fluid composed of an exciton donor/acceptor network capable of efficient EET [27–29] …”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…By probing the CPE photophysics, we can directly elucidate how the delocalized electronic wavefunction of the CPE evolves across the transition from the two‐phase to the one‐phase region of the phase diagram. To the best of our knowledge, our work is the first to demonstrate the formation of an aqueous complex fluid composed of an exciton donor/acceptor network capable of efficient EET [27–29] …”
Section: Introductionmentioning
confidence: 92%
“…To the best of our knowledge, our work is the first to demonstrate the formation of an aqueous complex fluid composed of an exciton donor/ acceptor network capable of efficient EET. [27][28][29]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The melt intractability and limited solubility of conjugated polymers have restricted the processing of these materials, hindering the fabrication of bulk/shaped structures that are required in various applications such as actuators, bioelectronic scaffolds, or thermoelectric modules. Recently, solvated mixtures of a conjugated polyelectrolyte (CPE) and an oppositely charged insulating polymer have been demonstrated to form fluid- or gel-like complex coacervates that can be processed at very high polymer loading. Electrostatic interactions have previously been utilized to improve the processability of conjugated polymers in water, such as the widely investigated interpolymer complexes poly­(3,4-ethylenedioxythiophene)/poly­(styrenesulfonate) (PEDOT:PSS) and polyaniline/poly­(2-acryl amido-2-methyl-1-propanesulfonic acid) (PANI:PAAMPSA). In these systems, the conjugated monomers are polymerized on the polymer acid templates, where the hydrophilic nature of the template forms a shell that stabilizes the hydrophobic conjugated core in water.…”
Section: Experiments: Compatibilizing the Incompatiblementioning
confidence: 99%
“…The Segalman and Chabinyc groups have also shown that oppositely charged systems with one conjugated and one non-conjugated polyelectrolyte can be used to form semiconducting and conducting fluids. [27,28] In this work, we have used aqueous associative phase separation to form complex fluids composed of two oppositely charged CPEs which function as an exciton donor/acceptor pair. We find spectrally broad light absorption and highly efficient exciton transfer from the donor to the acceptor CPE.…”
Section: Introductionmentioning
confidence: 99%